Родительский дом: повести и рассказы / Сергей Воронин ; [художник В. Мясоедов] - Воронин Сергей Алексеевич (Современник, 1987)
Экземпляры: ф.11 (20200317) / Инвентарный номер: 15194 / Авт.знак: В 75 / ГРНТИ: 17.82 / ББК: 84(2 Рос=Рус)6